Bi-layer diaphragm walls: structural and sectional analysis - Segura-Castillo, Luis; Aguado, Antonio; De La Fuente Antequera, Albert; Josa, Alejandro (Journal of Civil Engineering and Management, 2016)
The bi-layer diaphragm wall, a new slurry wall type designed to cope with the problem of watertightness is studied in this paper. These walls consist of two bonded concrete layers, the first, a conventional Reinforced Concrete (RC) diaphragm wall, and the second, a Sprayed Steel Fibre Reinforced Concrete (SFRC). The main objective of this paper is to analyze the structural and sectional behaviour of these walls. A study in the form of an uncoupled structural-section analysis based on various hypothetical cases of bi-layer diaphragm walls was performed to fulfil the objective. It is concluded that there exists a potential of reduction in the reinforcement of the RC layer through the structural use of the SFRC layer. However, when the reduction is quantified, even though a reduction of between 3.2% and 1.7% in the RC reinforcement is confirmed, it appears insufficient to offer a cost-effective solution. Nonetheless, the system becomes a promising solution when particular conditions are taken into account, such as basement space limitations. First published online: 04 Sep 2015